Ubon Ratchathani’s Cathedral of the Immaculate Conception: Modern Roman Catholic Architecture in Thailand - Pundi, Supawan (NAJUA: History of Architecture and Thai Architecture, 2022)
This paper studies the architecture and design work of Ubon Ratchathani’s Cathedral of the Immaculate Conception which was designed by Professor Emeritus Captain Krisda Arunvongse Na Ayudhya in 1960. Drawing upon the architect’s archives and interviews with those involved in the project, the paper places the unique characteristics of this example of modern Roman Catholic architecture in the context of the national development of the 1960s. More specifically it argues that the Cathedral’s design is best understood in relation to the policies of the Thai Government and Southeast Asia Treaty Organization (SEATO) which focused on economic and social development and the holding of the Second Vatican Council which established the conceptual framework of creating sacred spaces reflecting modern Roman Catholic architecture. Lastly, the architect’s experimentation of a hyperbolic paraboloid design introduced international modern architectural design to rural Thailand. The findings will, it is hoped, broaden our understanding of the development of modern architecture in Thailand.